Protooncogenes as mediators of apoptosis - Teng, Ching-Sung (International Review of Cytology, 2000)
Apoptosis has been well established as a vital biological phenomenon that is important in the maintenance of cellular homeostasis. Three major protooncogene families and their encoded proteins function as mediators of apoptosis in various cell types and are the subject of this chapter. Protooncogenic proteins such as c-Myc/Max, c-Fos/c-Jun, and Bcl-2/Bax utilize a synergetic effect to enhance their roles in the pro- or antiapoptotic action. These family members activate and repress the expression of their target genes, control cell cycle progression, and execute programmed cell death. Repression or overproduction of these protooncogenic proteins induces apoptosis, which may vary as a result of either cell type specificity or the nature of the apoptotic stimuli. The proapoptotic and antiapoptotic proteins exert their effects in the membrane of cellular organelles. Here they generate cell-type-specific signals that activate the caspase family of proteases and their regulators for the execution of apoptosis.